ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA PADA MATERI TRIGONOMETRI - Iyam Maryati; Cindy Elsa Parani (Department of Mathematics Education, Universitas Kuningan, 2021)
This study aims to find out the level of mathematical creative thinking ability of students in solving trigonometry problems. This research approach is a qualitative approach of descriptive type. Data collection techniques are carried out using test methods, interviews and documentation. Data validity test is done by triangulation technique. Data is analyzed using data reduction, data presentation, and inference. The research instrument used is a test of mathematical creative thinking ability. The results of this study, from 12 random high school grade XI students who have taken the test online, as many as 3 people get grades in high categories, as many as 3 people get grades in the moderate category, and as many as 6 people who score in low categories. From the test data and interviews, from the data can be known that the mathematical creative thinking ability of most students of grade XI random high school in Garut district is said to be very low.